Polishing pad and method for manufacturing the same
Patent Information
- Application Number
- JP2026097269
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-11-06
- Filing Date
- 2026-06-10
- Publication Date
- 2026-09-08
AI Technical Summary
【0010】 実現例による研磨パッドは、ウェーハと接触して研磨を行うトップパッドと、前記トップパッドの一面に位置するサブパッドとを含み、シリコンオキサイド膜に対するCMP工程研磨率プロファイルにおいて、ウェーハの中心からの距離が85mmであるポイントにおける研磨率よりも、ウェーハの中心からの距離が95mmであるポイントにおける研磨率がより大きい値を有することにより、研磨率および研磨平坦度を向上させることができ、特に、研磨パッドエッジ(egde)の研磨率プロファイル特性に優れる。
Smart Images

Figure 2026143695000002 
Figure 2026143695000003 
Figure 2026143695000004
Abstract
Description
[Technical Field]
[0001] The example concerns polishing pads used in the chemical mechanical polishing (CMP) process of semiconductor devices, and more specifically, polishing pads and methods for manufacturing the same. [Background technology]
[0002] In the semiconductor manufacturing process, chemical mechanical polishing (CMP) is a process in which a semiconductor substrate, such as a wafer, is attached to a head and brought into contact with the surface of a polishing pad fixed on a platen, and the platen and the head are moved relative to each other to flatten the uneven surface of the semiconductor substrate.
[0003] In such a CMP process, the polishing pad significantly affects the surface finish quality of the semiconductor substrate, and therefore requires stable physical properties. In particular, the polishing rate of the CMP process can change sensitively depending on the components and physical properties contained in the polishing pad, so it is necessary to optimize the components and physical properties contained in the polishing pad.
[0004] On the other hand, a polishing pad may consist of a top pad that contacts the wafer and performs polishing, and a sub-pad located below the top pad and supporting the tap pad. The sub-pad may be used to absorb and disperse the impact applied to the top pad, or to improve characteristics such as the polishing rate. However, there are limitations to how much such characteristics can be improved by such a sub-pad. Therefore, research is ongoing to further improve characteristics such as the polishing rate of the polishing pad using the sub-pad. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Korean Patent Publication No. 2018-0044771 [Overview of the project] Problem to be Solved by the Invention
[0006] Accordingly, an embodiment provides a polishing pad capable of improving polishing rate and polishing flatness by including a specific subpad at a lower portion of a top pad without degrading physical properties and the like of the top pad, and a method for manufacturing the same. Means for Solving the Problem
[0007] A polishing pad according to one embodiment includes a top-pad that contacts a wafer for polishing, and a sub-pad positioned on one surface of the top-pad, and satisfies Formula 1 below. [Formula 1] RR 85 <RR 95 In Formula 1 above, RR 85 is the polishing rate (Å / min) at a point where the distance from the center of the wafer is 85 mm in a CMP process polishing rate profile for a silicon oxide film, RR 95 is the polishing rate (Å / min) at a point where the distance from the center of the wafer is 95 mm in a CMP process polishing rate profile for a silicon oxide film.
[0008] A method for manufacturing a polishing pad according to another embodiment includes the steps of: (1) manufacturing a top pad using a top pad composition containing a urethane-based prepolymer, a foaming agent, and a curing agent; (2) manufacturing a subpad including a non-woven fabric layer and a suede layer; and (3) bonding the top pad and the subpad together to manufacture a polishing pad, wherein the polishing pad satisfies Formula 1 above.
[0009] A method for manufacturing a semiconductor device according to still another embodiment includes the step of polishing a surface of a semiconductor substrate using the polishing pad described above. Effect of the Invention
[0010] The polishing pad in the implemented example includes a top pad that contacts the wafer to perform polishing and a sub-pad located on one surface of the top pad. In the CMP process polishing rate profile for the silicon oxide film, the polishing rate at a point 95 mm from the center of the wafer is greater than the polishing rate at a point 85 mm from the center of the wafer, thereby improving the polishing rate and polishing flatness. In particular, it exhibits excellent polishing rate profile characteristics at the polishing pad edge (egde).
[0011] More specifically, the sub-pad has a double-layer structure including a nonwoven fabric layer and a suede layer. By controlling the physical properties of the sub-pad, such as hardness, compressibility, and density, it satisfies a positive gradient value in the CMP process polishing profile, unlike conventional polishing pads where the gradient value at a distance of 85mm to 95mm from the center of the wafer is a negative number. Therefore, the polishing efficiency of the polishing pad can be improved, and it has excellent polishing flatness, especially because of the superior polishing efficiency profile characteristics of the polishing pad edge.
[0012] Furthermore, the polishing pads used in the implementation examples can improve the polishing rate and polishing flatness without degrading the physical properties or processability of the polishing pads. Therefore, when using them in the manufacturing of semiconductor devices, CMP performance and yield can be improved. [Brief explanation of the drawing]
[0013] [Figure 1] Figure 1 shows a scanning electron microscope (SEM) image of the sub-pad cross-section in Example 1. [Figure 2] Figure 2 shows a scanning electron microscope (SEM) image of the sub-pad cross-section in Comparative Example 1. [Figure 3] Figure 3 shows a scanning electron microscope (SEM) image of the sub-pad cross-section in Comparative Example 2. [Figure 4]Figure 4 shows the CMP polishing rate profile of the polishing pad in Example 1. [Figure 5] Figure 5 shows the CMP polishing rate profile of the polishing pad in Comparative Example 1. [Figure 6] Figure 6 shows the CMP polishing rate profile of the polishing pad in Comparative Example 2. [Figure 7] Figure 7 shows the CMP polishing rate profiles of the polishing pads in Example 1, Comparative Example 1, and Comparative Example 2 together. [Figure 8] Figure 8 shows the gradient of the CMP polishing rate profiles of the polishing pads in Example 1, Comparative Example 1, and Comparative Example 2 at a distance of 85 mm to 95 mm from the center of the wafer. [Figure 9] Figure 9 shows a schematic process diagram of a semiconductor device manufacturing process based on one implementation example. [Modes for carrying out the invention]
[0014] The invention will be described in detail below with reference to examples of its implementation. The examples of implementation are not limited to those disclosed below and can be modified in various forms as long as the gist of the invention is not altered.
[0015] In this specification, terms used to refer to each component are used to distinguish them from other components and are not intended to limit the examples of implementation. Furthermore, in this specification, singular expressions include plural expressions unless the context clearly indicates otherwise.
[0016] In this specification, the statement that a part "includes" a certain component means, unless otherwise stated, that it may include other components rather than excluding them.
[0017] In this specification, any description of one component being formed above / below another, or being connected or joined to one another, includes all instances of direct or indirect formation, connection, or joining between these components. Furthermore, the criteria for above / below each component should be understood to vary depending on the direction from which the object is observed.
[0018] All numerical ranges indicating physical properties, dimensions, etc., of the constituent components described herein should be understood to be modified by the term "approximately" in all cases, unless otherwise specified.
[0019] In the numerical ranges that limit the size, physical properties, etc., of the components described herein, if numerical ranges limited only by upper limits and numerical ranges limited only by lower limits are given as separate examples, it should be understood that the numerical ranges formed by combining these upper and lower limits are also included in the exemplary ranges.
[0020] [Polishing pad] A polishing pad according to one example includes a top pad that contacts the wafer to perform polishing and a sub-pad located on one surface of the top pad, and satisfies the following formula 1. [Formula 1] RR 85 <RR 95 In the above formula 1, RR 85 This is the polishing rate (Å / min) at a point 85 mm from the center of the wafer in the CMP process polishing rate profile for silicon oxide films. RR 95 This represents the polishing rate (Å / min) at a point 95 mm from the center of the wafer in the CMP process polishing rate profile for silicon oxide films.
[0021] Specifically, top pads, which are generally manufactured using polyurethane material, have viscoelastic properties, which can lead to uneven pressure distribution during the CMP process, causing the pad to deform. In particular, strong pressure applied to prevent wafer detachment can cause a rebounding shape, which can degrade the edge polishing profile characteristics in the CMP process polishing profile.
[0022] In one example, the polishing pad improves the CMP process polishing rate profile characteristics, more specifically the edge polishing rate profile characteristics, by providing a sub-pad on one surface of the top pad that contacts the wafer for polishing, and by controlling the type and characteristics of the sub-pad, the viscoelastic properties of the top pad can be effectively controlled. Therefore, in the CMP process polishing rate profile for a silicon oxide film, the polishing rate at a point 95 mm from the center of the wafer is greater than the polishing rate at a point 85 mm from the center of the wafer, thereby improving the polishing rate and polishing flatness, and in particular, it has excellent polishing rate profile characteristics at the edge of the polishing pad.
[0023] According to one implementation example, the polishing pad has a positive average gradient value in the CMP process polishing rate profile for a silicon oxide film, where the distance from the center of the wafer is between 85 mm and 95 mm.
[0024] For example, in the CMP process removal rate profile for a silicon oxide film, the average gradient value at a distance of 85 mm to 95 mm from the center of the wafer is 0.1 or more, 0.3 or more, 0.5 or more, 0.8 or more, 1.0 or more, 1.2 or more, 1.5 or more, 2 or more, 3 or more, 3.5 or more, 4 or more, 5.5 or more, 6 or more, 7 or more, 8 or more, 9.5 or more, 10.5 or more, 11 or more, 12 or more, 13.5 or more, or 15 or more, and may be 1.5 to 15, 2 to 11.5, 3 to 10.5, 4.5 to 9, or 5 to 8.5. When the average gradient value at a distance of 85 mm to 95 mm from the center of the wafer in the CMP process removal rate profile for a silicon oxide film satisfies the above range, the removal rate and polishing flatness can be further improved.
[0025] In addition, the polishing pad may have a removal rate difference (ΔRR) according to Formula 2 below of 200 Å / min or less. [Formula 2] ΔRR=RR 95 -RR 85 In Formula 2 above, RR 85 is the removal rate (Å / min) at a point where the distance from the center of the wafer is 85 mm in the CMP process removal rate profile for a silicon oxide film, RR 95 is the removal rate (Å / min) at a point where the distance from the center of the wafer is 95 mm in the CMP process removal rate profile for a silicon oxide film.
[0026] For example, the removal rate difference (ΔRR) according to Formula 2 above may be 180 Å / min or less, 150 Å / min or less, 120 Å / min or less, 100 Å / min or less, 80 Å / min or less, or 50 Å / min or less. The polishing pad according to one embodiment has excellent polishing uniformity when the removal rate difference according to Formula 2 above satisfies the above range.
[0027] In addition, the RR 85These ranges from 1950 Å / min to 3300 Å / min, 2000 Å / min to 3000 Å / min, 2100 Å / min to 2950 Å / min, 2250 Å / min to 2900 Å / min, or 2300 Å / min to 2650 Å / min, and the aforementioned RR 95 This could be 2000 Å / min to 3500 Å / min, 2150 Å / min to 3350 Å / min, 2200 Å / min to 3200 Å / min, or 2350 Å / min to 3000 Å / min.
[0028] Furthermore, when polishing the silicon oxide layer of a silicon wafer with a ceria slurry using the aforementioned polishing pad, the average polishing rate according to the following mathematical formula 1 can be 2100 Å / min to 3500 Å / min. [Mathematics 1] Average polishing rate (Å / min) = Change in film thickness before and after polishing (Å) / Polishing time (min)
[0029] For example, when polishing a silicon oxide film on a silicon wafer with a ceria slurry using the polishing pad, the average removal rate may be 2100 Å / min to 3300 Å / min, 2150 Å / min to 3100 Å / min, 2200 Å / min to 2950 Å / min, or 2250 Å / min to 2800 Å / min.
[0030] Specifically, the polishing rate may be the polishing rate on a silicon wafer with a diameter of 300 mm on which silicon oxide has been deposited. Furthermore, the polishing rate may be measured while rotating the platen at 150 rpm for 60 seconds, with a polishing load of 4.0 psi and a polishing pad rotation speed of 150 rpm, while adding a calcined ceria slurry at a rate of 250 mL / min. The temperature conditions during the measurement of the polishing rate are not particularly limited, but may, for example, be room temperature.
[0031] Furthermore, the polishing pad may have a polishing flatness (WIWNU) of 10% or less relative to the oxide. For example, the polishing flatness of the polishing pad relative to the oxide may be 9% or less, 7% or less, 5% or less, 4% or less, or 3% or less.
[0032] The aforementioned polishing flatness can be calculated using the following mathematical formula 2. [Math 2] Polishing flatness (%) = (Standard deviation of polished thickness (Å) / Average polished thickness (Å)) × 100
[0033] <Sub-pad> The polishing pad according to one embodiment includes a sub-pad. Specifically, the sub-pad is located on one surface below the top pad. More specifically, the sub-pad supports the top pad, i.e., the polishing layer, and absorbs and disperses external impacts applied to the polishing layer, thereby minimizing the occurrence of damage and defects to the object being polished during the polishing process to which the polishing pad is applied.
[0034] The sub-pad has a structure in which multiple pores are formed, and these pores may, but are not limited to, an open-cell structure. Furthermore, the sub-pad may be slightly softer because its pore formation rate is higher than that of the top pad and its hardness is lower than that of the top pad.
[0035] According to one implementation example, the sub-pad includes a nonwoven fabric layer and a suede layer. Specifically, the sub-pad includes a suede layer on the nonwoven fabric layer, and the suede layer may be located on one surface of the top pad. More specifically, the polishing pad has a structure in which the top pad is laminated on the sub-pad, and may have a structure in which the nonwoven fabric layer / suede layer / top pad are laminated.
[0036] The nonwoven fabric layer may be a resin-impregnated nonwoven fabric layer. For example, the nonwoven fabric layer may be a fiber nonwoven fabric layer containing one or more fibers selected from the group consisting of polyester fibers, polyamide fibers, polypropylene fibers, and polyethylene fibers.
[0037] Furthermore, the resin impregnated in the nonwoven fabric layer may include one or more resins selected from the group consisting of polyurethane resin, polybutadiene resin, styrene-butadiene copolymer resin, styrene-butadiene-styrene copolymer resin, acrylonitrile-butadiene copolymer resin, styrene-ethylene-butadiene-styrene copolymer resin, silicone rubber resin, polyester elastomer resin, and polyamide elastomer resin.
[0038] The suede layer can be bonded to the nonwoven fabric layer to form a sub-pad. Specifically, the suede layer can be formed by casting resin onto the nonwoven fabric layer.
[0039] The resin that can be used in the production of the suede layer may include one or more resins selected from the group consisting of polyurethane resin, polybutadiene resin, styrene-butadiene copolymer resin, styrene-butadiene-styrene copolymer resin, acrylonitrile-butadiene copolymer resin, styrene-ethylene-butadiene-styrene copolymer resin, silicone rubber resin, polyester elastomer resin, and polyamide elastomer resin.
[0040] The thickness ratio of the nonwoven fabric layer to the suede layer may be 1:0.5 to 2. For example, the thickness ratio of the nonwoven fabric layer to the suede layer may be 1:0.7 to 1.8, 1:0.9 to 1.5, 1:1 to 1.2, 1:0.7 to 0.9, or 1:1.5 to 1.8.
[0041] The sub-pad may have a thickness of 0.5 mm to 2.5 mm. For example, the total thickness of the sub-pad may be 0.6 mm or more, 0.7 mm or more, 0.85 mm or more, 0.95 mm or more, 1 mm or more, 1.1 mm or more, 1.3 mm or more, or 1.5 mm or more, and may range from 0.5 mm to 2.3 mm, 0.6 mm to 2.15 mm, 0.8 mm to 2 mm, 1 mm to 1.9 mm, 1.2 mm to 1.9 mm, or 1.3 mm to 1.85 mm.
[0042] Furthermore, the sub-pad may have a hardness of 60 Shore D to 90 Shore D. For example, the hardness of the sub-pad may be 62 Shore D to 85 Shore D, 65 Shore D to 85 Shore D, or 65 Shore D to 83 Shore D.
[0043] The sub-pad may have a compression ratio of 5% to 15%. For example, the compression ratio of the sub-pad may be 5.5% to 13%, 6% to 11.5%, 6.5% to 10%, or 7% to 9%.
[0044] Specifically, the sub-pad was cut into 5cm x 5cm sections, and the thickness (A) was measured after placing an 85g weight on it for 30 seconds using a dial thickness gauge (129-E, YASUDA Co., Ltd.), and the thickness (B) was measured after placing an additional 800g weight (85g weight + 800g weight) on it for 3 minutes. The compression ratio was then calculated using the following mathematical formula 3. [Math 3] Compression ratio (%) = [(AB) / A] × 100
[0045] Furthermore, the sub-pad has a density of 0.25 g / cm³. 3 ~0.7g / cm 3 This is possible. For example, the density of the sub-pad may be 0.25 g / cm³. 3 ~0.65g / cm 3 , 0.3g / cm³ 3 ~0.65g / cm 3 , or 0.3 g / cm³ 3 ~0.6g / cm 3 It is possible.
[0046] The aforementioned sub-pad may have a compressive modulus of 70% to 90%. For example, the compressive modulus may be 72% to 88% or 75% to 85%.
[0047] Specifically, the compression modulus refers to the degree to which the material recovers after being compressed. The sub-pad was cut into 5cm x 5cm sections, and the thickness (A) was measured after placing an 85g weight on it for 30 seconds using a dial thickness gauge (129-E, YASUDA Co., Ltd.). The thickness (C) was then measured after placing an additional 800g weight (85g weight + 800g weight) on it for 3 minutes, removing the 800g weight, and letting it sit for 1 minute. The compression modulus was then calculated using the following mathematical formula 4. [Math 4] Compression modulus (%) = [C / A] × 100
[0048] Compared to subpads consisting of a single layer of nonwoven fabric or suede, the aforementioned subpad has a lower density despite its greater thickness, and its hardness, compressibility, and compressive modulus are controlled within a favorable range. As a result, the polishing rate is uniformly distributed with respect to the distance from the center in the CMP process polishing rate profile, improving polishing flatness, and in particular improving the polishing rate profile characteristics of the polishing pad edge.
[0049] Furthermore, an adhesive layer may be inserted between the top pad and the sub-pad. The adhesive layer may include a hot-melt adhesive. The hot-melt adhesive may be one or more selected from the group consisting of polyurethane resins, polyester resins, ethylene-vinyl acetate resins, polyamide resins, and polyolefin resins. As a specific example, the hot-melt adhesive may be one or more selected from the group consisting of polyurethane resins and polyester resins.
[0050] Furthermore, double-sided tape is attached to the lower part of the support layer, and when applying it to the CMP device, the release paper of the double-sided tape can be removed and it can be attached to the platen for use.
[0051] <Top pad> A polishing pad according to one implementation example includes a top pad. Specifically, the top pad is configured to polish in contact with the wafer and includes a polishing layer. More specifically, the top pad includes a polishing layer containing a polyurethane resin.
[0052] The polishing layer comprises a urethane-based prepolymer, a foaming agent, and a curing agent. Specifically, the polyurethane resin is obtained from a composition comprising a urethane-based prepolymer, a foaming agent, and a curing agent.
[0053] More specifically, the polishing layer contains a polyurethane resin which is a reaction product of a urethane prepolymer, a foaming agent, and a curing agent, i.e., a cured product of a composition in which the components are mixed, thereby containing a porous polyurethane resin. The polishing layer may also contain a number of pores formed from the foaming agent.
[0054] The thickness of the polishing layer is, for example, 0.8 mm or more, 1 mm or more, 1.2 mm or more, or 1.5 mm or more, and may be 5 mm or less, 3 mm or less, 2.5 mm or less, or 2 mm or less. As a specific example, the thickness of the polishing layer may be 0.8 mm to 5 mm, or 1.5 mm to 3 mm.
[0055] The specific gravity of the abrasive layer is, for example, 0.6 g / cm³. 3 More than 0.7g / cm 3 Above, or 0.75 g / cm³ 3 The above is 0.9 g / cm³. 3 Below, 0.85g / cm 3 The following, or 0.8 g / cm³ 3 The following is possible. As a specific example, the specific gravity of the polishing layer is 0.6 g / cm³. 3 ~0.9g / cm 3 , or 0.7 g / cm³ 3 ~0.9g / cm 3 It is possible.
[0056] The hardness of the abrasive layer is, for example, 30 Shore D or higher, 40 Shore D or higher, or 50 Shore D or higher, and may be 80 Shore D or lower, 70 Shore D or lower, 65 Shore D or lower, or 60 Shore D or lower. As a specific example, the hardness of the abrasive layer may be between 30 Shore D and 80 Shore D or between 50 Shore D and 65 Shore D.
[0057] The tensile strength of the polished layer is, for example, 5 N / mm². 2 More than 10N / mm 2 Above or above, or 15 N / mm 2 That's all. 30 N / mm 2 Below, 25N / mm 2 The following, or 20 N / mm² 2 The following is possible. As a specific example, the tensile strength of the polished layer is 5 N / mm². 2 ~30N / mm 2 , or 15 N / mm 2 ~25N / mm 2 It is possible.
[0058] The elongation rate of the abrasive layer may be, for example, 50% or more, 70% or more, 90% or more, 106% or more, or 120% or more, and may be 300% or less, 250% or less, 200% or less, or 150% or less. As a specific example, the elongation rate of the abrasive layer may be 50% to 300% or 90% to 130%. The elongation rate may be the elongation rate at break.
[0059] As a specific example, the polishing layer has a hardness of 50 Shore D to 65 Shore D and a density of 15 N / mm². 2 ~25N / mm 2 It can have a tensile strength and an elongation of 90% to 130%.
[0060] The aforementioned pores are dispersed within the polished layer. The average diameter of the pores may be, for example, 10 μm to 60 μm, 10 μm to 50 μm, 20 μm to 50 μm, 20 μm to 40 μm, 10 μm to 30 μm, 20 μm to 25 μm, or 30 μm to 50 μm.
[0061] Furthermore, the total surface area of the pores may be 30% to 60%, 35% to 50%, or 35% to 43% of the total surface area of the polished layer. Also, the total volume of the pores may be 30% to 70% or 40% to 60% of the total volume of the polished layer.
[0062] The abrasive layer may have grooves on its surface for mechanical polishing. The grooves may have, and are not particularly limited, an appropriate depth, width, and spacing for mechanical polishing.
[0063] One example of a polishing pad contains a urethane-based prepolymer. A prepolymer generally refers to a polymer with a relatively low molecular weight whose degree of polymerization has been stopped at an intermediate stage to facilitate molding in the production of certain final molded products. Prepolymers can be molded on their own or after reacting with other polymerizable compounds; for example, a prepolymer can be prepared by reacting an isocyanate compound with a polyol.
[0064] The isocyanate compound used in the preparation of the urethane-based prepolymer may be one selected from the group consisting of aromatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, and combinations thereof.
[0065] The isocyanate compound may include, for example, one selected from the group consisting of toluene 2,4-diisocyanate (2,4-TDI), toluene 2,6-diisocyanate (2,6-TDI), naphthalene-1,5-diisocyanate, para-phenylenediisocyanate, tolidine diisocyanate, 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, and combinations thereof.
[0066] The polyol is a compound containing at least two hydroxyl groups (-OH) per molecule, and may include, for example, one selected from the group consisting of polyether polyols, polyester polyols, polycarbonate polyols, polycaprolactone polyols, and combinations thereof.
[0067] The polyol may include, for example, one selected from the group consisting of polytetramethylene ether glycol, polypropylene ether glycol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, tripropylene glycol, and combinations thereof.
[0068] The polyol may have a weight-average molecular weight (Mw) of 100 g / mol to 3000 g / mol. For example, the weight-average molecular weight of the polyol may be 100 g / mol to 3000 g / mol, 100 g / mol to 2000 g / mol, or 100 g / mol to 1800 g / mol.
[0069] According to one example, the polyol may include low molecular weight polyols with a weight-average molecular weight (Mw) of 100 g / mol to 300 g / mol and high molecular weight polyols with a weight-average molecular weight (Mw) of 300 g / mol to 1800 g / mol.
[0070] Furthermore, the urethane-based prepolymer may have a weight-average molecular weight of 500 g / mol to 3000 g / mol. For example, the weight-average molecular weight of the urethane-based prepolymer may be 500 g / mol to 2500 g / mol, 1000 g / mol to 2000 g / mol, or 1000 g / mol to 1500 g / mol.
[0071] According to one example, the isocyanate compound for preparing the urethane-based prepolymer includes an aromatic diisocyanate compound, which may include, for example, 2,4-toluene diisocyanate (2,4-TDI) and 2,6-toluene diisocyanate (2,6-TDI). The polyol compound for preparing the urethane-based prepolymer may include polytetramethylene ether glycol (PTMEG) and diethylene glycol (DEG).
[0072] In other realizations, the isocyanate compound for preparing the urethane-based prepolymer may include aromatic diisocyanate compounds and alicyclic diisocyanate compounds. For example, the aromatic diisocyanate compound may include 2,4-toluene diisocyanate (2,4-TDI) and 2,6-toluene diisocyanate (2,6-TDI), and the alicyclic diisocyanate compound may include dicyclohexylmethane diisocyanate (H12MDI). The polyol compound for preparing the urethane-based prepolymer may include polytetramethylene ether glycol (PTMEG) and diethylene glycol (DEG).
[0073] The urethane-based prepolymer has an isocyanate end group content (NCO%) of 5% by weight or more, 8% by weight or more, or 10% by weight or more, and may also be 13% by weight or less, 12% by weight or less, or 11% by weight or less. As a specific example, the urethane-based prepolymer may have an isocyanate end group content (NCO%) of 8% to 11% by weight or 9% to 10% by weight.
[0074] The isocyanate end group content (NCO%) of the urethane-based prepolymer can be designed by comprehensively adjusting the type and content of the isocyanate compound and polyol compound used to prepare the urethane-based prepolymer, the process conditions such as temperature, pressure, and time for the preparation of the urethane-based prepolymer, and the type and content of the additives used in the preparation of the urethane-based prepolymer.
[0075] When the isocyanate end group content (NCO%) of the urethane-based prepolymer satisfies the above range, the reaction rate, reaction time, and final cured structure during the subsequent reaction between the urethane-based prepolymer and the curing agent can be adjusted in a direction advantageous to the polishing performance of the final polishing pad according to its application and intended use.
[0076] According to one example, the isocyanate end group content (NCO%) of the urethane-based prepolymer can be 8% to 11% by weight or 9% to 10% by weight.
[0077] If the NCO% is below the range, the desired polishing performance may not be achieved in terms of polishing rate and flatness due to the electrical properties based on the chemically hardened structure within the polishing pad, and there may be problems such as a reduction in the lifespan of the polishing pad due to an excessive increase in the cutting rate. On the other hand, if the NCO% exceeds the range, surface defects such as scratches and chatter marks on the semiconductor substrate may increase.
[0078] The foaming agent may include one selected from the group consisting of solid-phase foaming agents, gas-phase foaming agents, liquid-phase foaming agents, and combinations thereof, as a component for forming a porous structure within the polished layer.
[0079] According to one example, the foaming agent is a non-chlorine foaming agent that does not contain chlorine components, and in particular, does not contain chlorine foaming agent components commonly used in the manufacture of polishing pads, such as vinylidene chloride (VDC), or its use can be minimized. For example, the content of the non-chlorine foaming agent based on the total weight of the foaming agent may be 50% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, 97% by weight or more, 99% by weight or more, or 99.5% by weight or more, and may also be 100% by weight or less, or 99.5% by weight or less. Specific examples include 80% to 100% by weight, 90% to 100% by weight, or 80% to 99.5% by weight. Furthermore, the content of the chlorine-based blowing agent relative to the total weight of the blowing agent is 20% by weight or less, 10% by weight or less, 5% by weight or less, 1% by weight or less, or 0.5% by weight or less, or 0.3% by weight or less, and also 0% by weight or more, 0.1% by weight or more, or 0.5% by weight or more. Specific examples include 0% to 20% by weight, 0% to 1% by weight, 0% to 0.5% by weight, or 0.5% to 20% by weight.
[0080] The blowing agent may be one or more selected from a solid-phase blowing agent containing hollow-structured particles, a liquid-phase blowing agent using a volatile liquid, and an inert gas.
[0081] As an example, the solid-phase foaming agent may contain hollow-structured particles whose size is adjusted by thermal expansion. Such a solid-phase foaming agent has the advantage of uniformly adjusting the particle size of the pores because it is added to the raw material in an already expanded form and has a uniform particle size.
[0082] Furthermore, the solid-phase foaming agent may contain expandable particles. These expandable particles are particles that have the property of being able to expand by heat or pressure, and their size in the final polished layer may be determined by the heat or pressure applied during the manufacturing process of the polished layer. The expandable particles may be added to the raw material in an unexpanded particle state beforehand, and their final size may be determined by the heat or pressure applied during the manufacturing process of the polished layer.
[0083] The average particle size of the solid-phase foaming agent is, for example, 5 μm to 100 μm, and specifically may be 5 μm to 50 μm or 20 μm to 50 μm. The average particle size of the solid-phase foaming agent refers to the average particle size of the expanded particles themselves when the solid-phase foaming agent is introduced into the raw materials in an expanded state as described later, and may refer to the average particle size of the particles after they have expanded due to heat or pressure during the manufacturing process when the solid-phase foaming agent is introduced into the raw materials in an unexpanded state as described later.
[0084] The aforementioned expandable particle type solid-phase foaming agent may include an outer shell made of resin material and an expansion-inducing component present inside the outer shell. Such expandable particles can be formed into a hollow structure by the vaporization of the internal expansion-inducing component due to heat during the manufacturing process.
[0085] For example, the outer shell may contain a thermoplastic resin. The thermoplastic resin may be one or more selected from the group consisting of acrylonitrile copolymers, methacrylonitrile copolymers, and acrylic copolymers.
[0086] The thickness of the outer layer is, for example, 0.1 μm or more, 0.5 μm or more, 1 μm or more, 2 μm or more, or 3 μm or more, and also 15 μm or less, 12 μm or less, or 10 μm or less, and as a specific example, it may be 2 μm to 15 μm.
[0087] The swelling-inducing component may include one selected from the group consisting of hydrocarbon compounds, tetraalkylsilane compounds, and combinations thereof. Specifically, the hydrocarbon compound may include one selected from the group consisting of ethane, ethylene, propane, propene, n-butane, isobutene, n-butene, isobutene, n-pentane, isopentane, n-hexane, heptane, petroleum ether, and combinations thereof. The tetraalkylsilane compound may include one selected from the group consisting of tetramethylsilane, trimethylethylsilane, trimethylisopropylsilane, trimethyl-n-propylsilane, and combinations thereof.
[0088] The solid-phase foaming agent may contain particles treated with inorganic components. In one embodiment, the solid-phase foaming agent may have a surface treated with silica (SiO2) particles. The inorganic component treatment of the solid-phase foaming agent can prevent aggregation between multiple particles. The inorganic-component-treated solid-phase foaming agent may have different chemical, electrical, and / or physical properties of the foaming agent surface compared to an inorganic-component-treated solid-phase foaming agent.
[0089] Examples of commercially available solid-phase foaming agents include Nouryon's 920DE20d70, 051DET40d25, 051DET40d42, etc., and Matsumoto's F-65DE, F-80DE, FN-80SDE, etc.
[0090] As a specific example, the foaming agent used in the polishing pad according to the above-mentioned embodiment includes a solid-phase foaming agent, and the solid-phase foaming agent may include one or more selected from the group consisting of acrylonitrile copolymers, methyl methacrylate copolymers, methacrylonitrile copolymers, and acrylic copolymers.
[0091] The content of the solid-phase foaming agent is 0.1 parts by weight or more, 0.5 parts by weight or more, or 1 part by weight or more, based on 100 parts by weight of the urethane-based prepolymer, and may also be 5 parts by weight or less, 3 parts by weight or less, or 2 parts by weight or less. As a specific example, the content of the solid-phase foaming agent may be 0.1 to 5 parts by weight or 0.5 to 2 parts by weight, based on 100 parts by weight of the urethane-based prepolymer.
[0092] The type and content of the solid-phase foaming agent can be designed according to the desired porosity structure and physical properties of the polished layer.
[0093] On the other hand, the liquid-phase foaming agent is introduced into the process of mixing and reacting the prepolymer and curing agent, and can form pores, but does not participate in the reaction between the prepolymer and the curing agent. Furthermore, the liquid-phase foaming agent physically vaporizes due to the heat generated during the mixing and reaction process of the prepolymer and curing agent, thereby forming pores.
[0094] The volatile liquid-phase foaming agent does not react with isocyanate groups, amide groups, and alcohol groups, and may be in the liquid phase at 25°C. Specifically, the volatile liquid-phase foaming agent can be selected from the group consisting of perfluoro compounds such as cyclopentane, n-pentane, cyclohexane, n-butyl acetate, bis(nonafluorobutyl)(trifluoromethyl)amine, and perfluorotributylamine, perfluoro-N-methylmorpholine, perfluorotripentylamine, and perfluorohexane. Examples of commercially available perfluoro compounds include 3M's FC-40, FC-43, FC-70, FC-72, FC-770, FC-3283, and FC-3284.
[0095] In addition, the blowing agent may include a gas-phase blowing agent. For example, the blowing agent may include a solid-phase blowing agent and a gas-phase blowing agent.
[0096] The gas-phase blowing agent may contain an inert gas. The gas-phase blowing agent may be added during the reaction between the urethane-based prepolymer and the curing agent and used as a pore-forming element.
[0097] The type of inert gas is not particularly limited, as long as it is a gas that does not participate in the reaction between the urethane-based prepolymer and the curing agent. For example, the inert gas may include one selected from the group consisting of nitrogen gas (N2), carbon dioxide gas (CO2), argon gas (Ar), helium gas (He), and combinations thereof.
[0098] The type and content of the gas-phase foaming agent can be designed according to the desired porosity structure and physical properties of the polished layer.
[0099] The inert gas may be introduced in a volume corresponding to 10% to 30% of the total volume of the composition. Specifically, the inert gas may be introduced in a volume corresponding to 15% to 30% of the total volume of the composition. Specifically, the gas-phase blowing agent may be injected through a predetermined injection line during the mixing process of the urethane-based prepolymer, the solid-phase blowing agent, and the curing agent. For example, the injection rate of the gas-phase blowing agent may be about 0.8 L / min to about 2.0 L / min, about 0.8 L / min to about 1.8 L / min, about 0.8 L / min to about 1.7 L / min, about 1.0 L / min to about 2.0 L / min, about 1.0 L / min to about 1.8 L / min, or about 1.0 L / min to about 1.7 L / min.
[0100] The curing agent is a compound for chemically reacting with the urethane-based prepolymer to form the final cured structure in the polished layer, and may include, for example, an amine compound or an alcohol compound. Specifically, the curing agent may include one selected from the group consisting of aromatic amines, aliphatic amines, aromatic alcohols, aliphatic alcohols, and combinations thereof.
[0101] According to one example, the curing agent may include a non-chlorine curing agent that does not contain chlorine components. For example, the content of the non-chlorine curing agent based on the total weight of the curing agent may be 50% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, 97% by weight or more, 99% by weight or more, or 99.5% by weight or more, and may also be 100% by weight or less, or 99.5% by weight or less. Specific examples include 80% to 100% by weight, 90% to 100% by weight, or 80% to 99.5% by weight. Furthermore, the content of the chlorine-based curing agent based on the total weight of the curing agent is 20% by weight or less, 10% by weight or less, 5% by weight or less, 1% by weight or less, or 0.5% by weight or less, or 0.3% by weight or less, and also 0% by weight or more, 0.1% by weight or more, or 0.5% by weight or more. Specific examples include 0% to 20% by weight, 0% to 1% by weight, 0% to 0.5% by weight, or 0.5% to 20% by weight.
[0102] The curing agent may be at least one selected from solid-phase curing agents and liquid-phase curing agents.
[0103] The solid-phase curing agent may contain an active hydrogen group. The solid-phase curing agent may contain an amine group (-NH2) as the active hydrogen group.
[0104] Furthermore, the solid-phase curing agent may be an ester compound having two or more benzene rings. Specifically, the solid-phase curing agent may contain two or more of the ester groups in its molecule.
[0105] The solid-phase hardening agent may have a weight-average molecular weight of, for example, 150 g / mol to 400 g / mol, 150 g / mol to 350 g / mol, 200 g / mol to 350 g / mol, 250 g / mol to 350 g / mol, or 300 g / mol to 350 g / mol. Furthermore, the solid-phase hardening agent may have a melting point (mp) of 100°C to 150°C, 100°C to 140°C, or 110°C to 130°C.
[0106] In one example, the solid-phase curing agent may include one or more selected from the group consisting of 1,3-propanediol bis(4-aminobenzoate) (PDPAB), 4-(4-aminobenzoyl)oxyphenyl 4-aminobenzoate, 4-(4-aminobenzoyl)oxybutyl 4-aminobenzoate, 4-[4-(4-aminobenzoyl)oxy-3-methylbutoxy]butyl 4-aminobenzoate, and methylene bis-methylanthranilate (MBNA).
[0107] The liquid-phase curing agent may contain an active hydrogen group. The liquid-phase curing agent may contain one or more active hydrogen groups selected from the group consisting of an amine group (-NH2), a hydroxide group (-OH), a carboxylic acid group (-COOH), an epoxy group, and combinations thereof, and specifically may contain an amine group (-NH2).
[0108] Furthermore, the liquid-phase curing agent may contain sulfur within its molecule, specifically two or more intramolecular sulfur elements.
[0109] The liquid-phase curing agent has a weight-average molecular weight of 50 to 300, for example, 100 to 250, for example, 150 to 250, or for example, 200 to 250.
[0110] Furthermore, the liquid-phase curing agent may be in the liquid phase at room temperature. Alternatively, the liquid-phase curing agent may have a boiling point (bp) of 160°C to 240°C, specifically 170°C to 240°C, or more specifically 170°C to 220°C.
[0111] Examples of the liquid-phase curing agent include one or more selected from the group consisting of 3,5-dimethylthio-2,6-diaminotoluene (DMTDA), 2,6-bis(methylthio)-4-methyl-1,3-benzenediamine, and N,N'-bis(sec-butylamino)diphenylmethane.
[0112] Furthermore, the curing agent may further contain other curing agents in addition to the liquid-phase curing agent and the solid-phase curing agent. The other curing agents may be, for example, one or more amine compounds and alcohol compounds. Specifically, the other curing agents may contain one or more compounds selected from the group consisting of aromatic amines, aliphatic amines, aromatic alcohols, and aliphatic alcohols.
[0113] For example, the other curing agent may be one or more selected from the group consisting of diaminodiphenyl methane, diaminodiphenyl sulfone, m-xylylene diamine, isophoronediamine, ethylenediamine, diethylenetriamine, triethylenetetramine, polypropylenediamine, polypropylenetriamine, ethyleneglycol, diethyleneglycol, dipropyleneglycol, butanediol, hexanediol, glycerin, and trimethylolpropane.
[0114] As a specific example, the curing agent may contain one or more selected from the group consisting of 4,4'-methylenebis(2-chloroaniline) (MOCA), diethyltoluenediamine (DETDA), 3,5-dimethylthio-2,6-diaminotoluene (DMTDA), 1,3-propanediolbis(4-aminobenzoate) (PDPAB), N,N'-bis(sec-butylamino)diphenylmethane, 2,6-bis(methylthio)-4-methyl-1,3-benzenediamine, 4-(4-aminobenzoyl)oxyphenyl 4-aminobenzoate, 4-(4-aminobenzoyl)oxybutyl 4-aminobenzoate, 4-[4-(4-aminobenzoyl)oxy-3-methylbutoxy]butyl 4-aminobenzoate, and methylenebis-methylanthranilate (MBNA).
[0115] The content of the curing agent is 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, or 20 parts by weight or more, based on 100 parts by weight of the urethane-based prepolymer, and may also be 50 parts by weight or less, 45 parts by weight or less, 40 parts by weight or less, 35 parts by weight or less, 30 parts by weight or less, or 25 parts by weight or less. Specifically, the content of the curing agent is 10 to 40 parts by weight, based on 100 parts by weight of the urethane-based prepolymer, and more specifically, may be 15 to 35 parts by weight or 15 to 25 parts by weight.
[0116] Furthermore, the equivalent ratio of the urethane-based prepolymer to the curing agent may be 1:0.5 to 2. For example, the equivalent ratio of the urethane-based prepolymer to the curing agent may be 1:0.5 to 1.5, 1:0.5 to 1.0, or 1:0.6 to 1.2.
[0117] The composition for producing the abrasive layer may further include other additives such as surfactants and reaction rate modifiers. The names "surfactant," "reaction rate modifier," etc., are arbitrary names based on the main role of the substance, and each of the relevant substances does not necessarily perform only the functions limited to the role indicated by that name.
[0118] The surfactant is not particularly limited as long as it is a substance that plays a role in preventing phenomena such as pore aggregation or overlapping. For example, the surfactant may include a silicone-based surfactant.
[0119] The surfactant may be used in an amount of 0.2 to 2 parts by weight based on 100 parts by weight of the urethane-based prepolymer. Specifically, the surfactant may be included in amounts of 0.2 to 1.9 parts by weight, 0.2 to 1.8 parts by weight, 0.2 to 1.7 parts by weight, 0.2 to 1.6 parts by weight, 0.2 to 1.5 parts by weight, or 0.5 to 1.5 parts by weight based on 100 parts by weight of the urethane-based prepolymer. Including the surfactant in amounts within the above ranges allows pores derived from the gas-phase blowing agent to be stably formed and maintained within the mold.
[0120] The reaction rate regulator plays a role in either accelerating or delaying the reaction, and depending on the purpose, a reaction accelerator, a reaction retarder, or both may be used. The reaction rate regulator may include a reaction accelerator. For example, the reaction accelerator may be one or more reaction accelerators selected from the group consisting of tertiary amine compounds and organometallic compounds.
[0121] Specifically, the reaction rate modifier may include one or more selected from the group consisting of triethylenediamine, dimethylethanolamine, tetramethylbutanediamine, 2-methyl-triethylenediamine, dimethylcyclohexylamine, triethylamine, triisopropanolamine, 1,4-diazabicyclo(2,2,2)octane, bis(2-methylaminoethyl) ether, trimethylaminoethylethanolamine, N,N,N,N,N''-pentamethyldiethylenetriamine, dimethylaminoethylamine, dimethylaminopropylamine, benzyldimethylamine, N-ethylmorpholine, N,N-dimethylaminoethylmorpholine, N,N-dimethylcyclohexylamine, 2-methyl-2-azanorbornene, dibutyltin dilaurate, stanas octoate, dibutyltin diacetate, dioctyltin diacetate, dibutyltin malate, dibutyltin di-2-ethylhexanoate, and dibutyltin dimercaptide. Specifically, the reaction rate modifier may include one or more selected from the group consisting of benzyldimethylamine, N,N-dimethylcyclohexylamine, and triethylamine.
[0122] The reaction rate modifier may be used in an amount of 0.05 to 2 parts by weight based on 100 parts by weight of the urethane-based prepolymer. Specifically, the reaction rate modifier may be used in an amount of 0.05 to 1.8 parts by weight, 0.05 to 1.7 parts by weight, 0.05 to 1.6 parts by weight, 0.1 to 1.5 parts by weight, 0.1 to 0.3 parts by weight, 0.2 to 1.8 parts by weight, 0.2 to 1.7 parts by weight, 0.2 to 1.6 parts by weight, 0.2 to 1.5 parts by weight, or 0.5 to 1 part by weight based on 100 parts by weight of the urethane-based prepolymer. When the reaction rate modifier is used within the above content range, the curing reaction rate of the prepolymer composition can be appropriately adjusted to form an abrasive layer having pores of a desired size and hardness.
[0123] [Manufacturing method for polishing pads] A method for manufacturing a polishing pad according to another example includes the steps of: (1) manufacturing a top pad using a top pad composition comprising a urethane-based prepolymer, a foaming agent, and a curing agent; (2) manufacturing a sub-pad comprising a nonwoven fabric layer and a suede layer; and (3) manufacturing a polishing pad by bonding the top pad and the sub-pad together, wherein the polishing pad satisfies formula 1.
[0124] Step (1) of manufacturing a top pad using a top pad composition containing a urethane-based prepolymer, a foaming agent, and a curing agent. Another example of a method for manufacturing a polishing pad includes the step (1) of manufacturing a top pad using a top pad composition comprising a urethane-based prepolymer, a foaming agent, and a curing agent.
[0125] The specific types and contents of the urethane-based prepolymer, curing agent, and blowing agent are as illustrated above.
[0126] As a specific example, the foaming agent includes a solid-phase foaming agent, the solid-phase foaming agent includes one or more selected from the group consisting of acrylonitrile copolymers, methyl methacrylate copolymers, methacrylonitrile copolymers, and acrylic copolymers, and the curing agent may include one or more selected from the group consisting of diethyltoluenediamine (DETDA), 3,5-dimethylthio-2,6-diaminotoluene (DMTDA), 1,3-propanediol bis(4-aminobenzoate) (PDPAB), N,N'-bis(sec-butylamino)diphenylmethane, 2,6-bis(methylthio)-4-methyl-1,3-benzenediamine, 4-(4-aminobenzoyl)oxyphenyl 4-aminobenzoate, 4-(4-aminobenzoyl)oxybutyl 4-aminobenzoate, 4-[4-(4-aminobenzoyl)oxy-3-methylbutoxy]butyl 4-aminobenzoate, and methylenebis-methylanthranilate (MBNA).
[0127] The top pad composition may be prepared by sequentially or simultaneously mixing a urethane-based prepolymer, a foaming agent, and a curing agent.
[0128] As an example, the step of preparing the top pad composition may be carried out by mixing a urethane-based prepolymer with a curing agent and then further mixing it with a foaming agent, or by mixing the urethane-based prepolymer with the foaming agent and then further mixing it with the curing agent.
[0129] As another example, urethane prepolymers, curing agents, and blowing agents may be added to the mixing process substantially at almost the same time, and if blowing agents, surfactants, and inert gases are further added, they may also be added to the mixing process substantially at almost the same time.
[0130] Another example is to pre-mix a urethane-based prepolymer, a foaming agent, and a surfactant, and then add the curing agent, or to add the curing agent and an inert gas together.
[0131] In the aforementioned mixing process, the urethane-based prepolymer and the curing agent are mixed to initiate the reaction, allowing the blowing agent and inert gas to be uniformly dispersed within the raw materials. At this time, a reaction rate regulator can intervene in the reaction between the urethane-based prepolymer and the curing agent from the initial stages to adjust the reaction rate. Specifically, the mixing can be carried out at a speed of 1000 rpm to 10000 rpm or 4000 rpm to 7000 rpm. This speed range may be more advantageous because it allows for uniform dispersion of the inert gas and blowing agent within the raw materials.
[0132] Furthermore, the step of preparing the top pad composition is carried out under conditions of 50°C to 150°C, and may be carried out under vacuum degassing conditions if necessary.
[0133] If the foaming agent includes a solid-phase foaming agent, the steps of preparing the top pad composition may include the steps of mixing the urethane-based prepolymer and the solid-phase foaming agent to prepare a first preliminary composition, and mixing the first preliminary composition with a curing agent to prepare a second preliminary composition.
[0134] The viscosity of the first preliminary composition may be approximately 1000 cps to 2000 cps, approximately 1000 cps to 1800 cps, approximately 1000 cps to 1600 cps, or approximately 1000 cps to 1500 cps at approximately 80°C.
[0135] If the blowing agent includes a gas-phase blowing agent, the steps of preparing the top pad composition may include preparing a third preliminary composition containing the urethane-based prepolymer and the curing agent, and preparing a fourth preliminary composition by injecting the gas-phase blowing agent into the third preliminary composition. In one embodiment, the third preliminary composition may further include a solid-phase blowing agent.
[0136] In one embodiment, the steps for manufacturing the polishing layer may include preparing a mold preheated to a first temperature, injecting the top pad composition into the preheated mold and curing it, and post-curing the cured top pad composition under a second temperature condition higher than the preheating temperature.
[0137] In one implementation example, the temperature difference between the first temperature and the second temperature is approximately 10°C to approximately 40°C, for example, approximately 10°C to approximately 35°C, or approximately 15°C to approximately 35°C. In one implementation example, the first temperature may be approximately 60°C to approximately 100°C, approximately 65°C to approximately 95°C, or approximately 70°C to approximately 90°C. In one implementation example, the second temperature may be approximately 100°C to approximately 130°C, for example, approximately 100°C to approximately 125°C, or approximately 100°C to approximately 120°C.
[0138] The step of curing the top pad composition at the first temperature may be carried out for about 5 to 60 minutes, about 5 to 40 minutes, about 5 to 30 minutes, or about 5 to 25 minutes.
[0139] The step of post-curing the top pad composition cured at the first temperature at the second temperature may be carried out for about 5 to 30 hours, about 5 to 25 hours, about 10 to 30 hours, about 10 to 25 hours, about 12 to 24 hours, or about 15 to 24 hours.
[0140] Subsequently, the step of injecting the top pad composition into the mold and allowing it to cure is performed under temperature conditions of 60°C to 120°C and a curing rate of 50 kg / m². 2 ~200kg / m 2 This can be done under pressure conditions.
[0141] Furthermore, the method for manufacturing the top pad may further include steps such as cutting the surface of the obtained top pad and processing grooves on the surface. Such steps can be carried out by conventional top pad manufacturing methods.
[0142] As a specific example, the method for manufacturing the top pad may include a step of processing at least one surface of the polishing layer. The step of processing at least one surface of the polishing layer may include at least one of the following steps: forming grooves on at least one surface of the polishing layer; turning at least one surface of the polishing layer; and roughening at least one surface of the polishing layer.
[0143] The grooves may include at least one of concentric grooves formed at predetermined intervals from the center of the polishing layer and radial grooves continuously connected from the center of the polishing layer to the edge of the polishing layer. The turning may be performed by removing the polishing layer to a predetermined thickness using a cutting tool. The roughening may be performed by processing the surface of the polishing layer with a sanding roller.
[0144] <Step (2) of manufacturing a sub-pad including a nonwoven fabric layer and a suede layer> Another example of a method for manufacturing an abrasive pad includes a step (2) of manufacturing a sub-pad including a nonwoven fabric layer and a suede layer.
[0145] Specifically, by first manufacturing the nonwoven fabric layer and then forming a suede layer on the nonwoven fabric layer, a sub-pad consisting of a double structure of a nonwoven fabric layer and a suede layer can be manufactured.
[0146] More specifically, step (2) includes the steps of impregnating a nonwoven fabric with a resin to produce a nonwoven fabric layer, and casting a resin onto one surface of the nonwoven fabric layer to form a suede layer.
[0147] First, the nonwoven fabric layer can be manufactured by impregnating a nonwoven fabric with a resin. The nonwoven fabric may be a fibrous nonwoven fabric containing one or more fibers selected from the group consisting of polyester fibers, polyamide fibers, polypropylene fibers, and polyethylene fibers. The impregnation resin may also contain one or more resins selected from the group consisting of polyurethane resin, polybutadiene resin, styrene-butadiene copolymer resin, styrene-butadiene-styrene copolymer resin, acrylonitrile-butadiene copolymer resin, styrene-ethylene-butadiene-styrene copolymer resin, silicone rubber resin, polyester elastomer resin, and polyamide elastomer resin.
[0148] Specifically, the nonwoven fabric layer can be formed by impregnating the fibrous nonwoven fabric with the impregnation resin. As a specific example, the nonwoven fabric layer is formed by impregnating polyester fibers with polyurethane resin and then drying, and the drying process can be carried out at 120°C to 150°C or 125°C to 145°C for 5 to 60 minutes or 5 to 30 minutes.
[0149] The suede layer can be formed by casting a resin onto the nonwoven fabric layer. For example, the suede layer can be formed by casting one or more resins selected from the group consisting of polyurethane resin, polybutadiene resin, styrene-butadiene copolymer resin, styrene-butadiene-styrene copolymer resin, acrylonitrile-butadiene copolymer resin, styrene-ethylene-butadiene-styrene copolymer resin, silicone rubber resin, polyester elastomer resin, and polyamide elastomer resin onto the manufactured nonwoven fabric layer. As a specific example, the suede layer can be formed by casting a polyurethane resin onto the nonwoven fabric layer and drying it, and the drying process can be carried out at 120°C to 150°C or 125°C to 145°C for 5 to 60 minutes or 5 to 30 minutes.
[0150] Furthermore, after the suede layer is formed on the nonwoven fabric layer, both sides of the surf pad, i.e., the outer surfaces of the nonwoven fabric layer and the suede layer, can be sanded. As a specific example, this can be done by processing the outer surfaces of the nonwoven fabric layer and the suede layer with a sanding roller.
[0151] <Step (3) of manufacturing a polishing pad by bonding the top pad and the sub pad together> Another example of a method for manufacturing a polishing pad includes the step (3) of bonding the top pad and the sub-pad together to manufacture the polishing pad.
[0152] For example, the top pad and the sub-pad may be bonded together using an adhesive layer. As a specific example, a polishing pad can be manufactured by placing the sub-pad below the top pad and bonding the top pad and the sub-pad together using a hot-melt adhesive.
[0153] The hot-melt adhesive may be one or more selected from the group consisting of polyurethane resins, polyester resins, ethylene-vinyl acetate resins, polyamide resins, and polyolefin resins. As a specific example, the hot-melt adhesive may be one or more selected from the group consisting of polyurethane resins and polyester resins.
[0154] Furthermore, double-sided tape is attached to the lower part of the support layer, and when applying it to the CMP apparatus, the release paper of the double-sided tape can be removed and attached to the platen for use.
[0155] [Manufacturing method for semiconductor element] Another example of a semiconductor device manufacturing method includes a step of polishing the surface of a semiconductor substrate using the polishing pad.
[0156] Specifically, the method for manufacturing the semiconductor element may include the steps of providing a polishing pad according to the embodiment, and polishing the surface of the semiconductor substrate by rotating the polishing surface of the polishing layer and the surface of the semiconductor substrate relative to each other so that they come into contact.
[0157] Figure 9 shows a semiconductor device manufacturing process using a polishing pad according to one implementation example. Referring to Figure 9, after mounting the polishing pad 100 according to one implementation example onto the platen 200, the semiconductor substrate 600 to be polished is placed on the polishing pad 100. At this time, the surface of the semiconductor substrate 600 to be polished is in direct contact with the polishing surface of the polishing pad 100. For polishing, polishing slurry 400 can be sprayed onto the polishing pad through a nozzle. The flow rate of the polishing slurry 400 supplied through the nozzle is approximately 10 cm³. 3 / min ~ approx. 1000cm 3 The range is selected according to the purpose within the minute range, for example, approximately 50 cm. 3 / min ~ approx. 500cm 3 It could be, but is not limited to, per minute.
[0158] Subsequently, the semiconductor substrate 600 and the polishing pad 100 rotate relative to each other, so that the surface of the semiconductor substrate 600 can be polished. In this case, the rotation direction of the semiconductor substrate 600 and the rotation direction of the polishing pad 100 may be the same direction or opposite directions. The rotation speeds of the semiconductor substrate 600 and the polishing pad 100 are selected according to the purpose, within a range of approximately 10 rpm to approximately 500 rpm, for example, approximately 30 rpm to approximately 200 rpm, but are not limited to this range.
[0159] The semiconductor substrate 600, while mounted on the polishing head 510, is pressed against the polishing surface of the polishing pad 100 with a predetermined load, and then its surface is polished. The load applied by the polishing head 510 to the surface of the semiconductor substrate 600 and the polishing surface of the polishing pad 100 is approximately 1 gf / cm². 2 ~About 1000gf / cm 2 The appropriate value is selected within the range depending on the purpose, for example, approximately 10 gf / cm³. 2~About 800gf / cm 2 It is possible, but not limited to this.
[0160] In one implementation example, the semiconductor substrate 600 to be polished may include an oxide film, a tungsten film, or a composite film thereof. Specifically, the semiconductor substrate 600 may include an oxide film, a tungsten film, or a composite film of an oxide film and a tungsten film. The composite film of an oxide film and a tungsten film may be a multilayer film in which the tungsten film is laminated on one surface of the oxide film, or a monolayer film in which an oxide region and a tungsten region are mixed within a single layer. As the object to be polished has such film properties and the polishing pad has the properties according to the implementation example, defects can be minimized in the semiconductor device manufactured by the semiconductor device manufacturing method.
[0161] In one embodiment, the method for manufacturing the semiconductor device may further include, in the step of polishing the object to be polished, a step of supplying either the oxide film polishing slurry or the tungsten film polishing slurry, or a step of sequentially supplying the oxide film polishing slurry and the tungsten film polishing slurry to the polishing surface.
[0162] For example, if the semiconductor substrate to be polished contains an oxide film, the method for manufacturing the semiconductor device may include a step of supplying the slurry for polishing the oxide film. If the semiconductor substrate contains a tungsten film, the method for manufacturing the semiconductor device may include a step of supplying the slurry for polishing the tungsten film. If the semiconductor substrate contains a composite film of an oxide film and a tungsten film, the method for manufacturing the semiconductor device may include a step of sequentially supplying the slurry for polishing the oxide film and the slurry for polishing the tungsten film to the polishing surface. In this case, depending on the process, the slurry for polishing the oxide film may be supplied first and then the slurry for polishing the tungsten film may be supplied later, or the slurry for polishing the tungsten film may be supplied first and then the slurry for polishing the oxide film may be supplied later.
[0163] In one embodiment, the method for manufacturing the semiconductor device may further include a step of processing the polishing surface of the polishing pad 100 with a conditioner 470 at the same time as polishing the semiconductor substrate 600, in order to maintain the polishing surface of the polishing pad 100 in a state suitable for polishing.
[0164] The polishing pad according to the above-mentioned embodiment has a chlorine content in its polishing layer adjusted to a specific range, which allows it to maintain excellent physical properties and performance while reducing the size of debris and minimizing the occurrence of defects and scratches during the CMP process. As a result, high-quality semiconductor devices can be efficiently manufactured using this polishing pad.
[0165] (Examples) The above will be further explained in detail by the following examples. However, the following examples are for illustrative purposes only, and the scope of the examples is not limited to these.
[0166] [Manufacturing of polishing pads] (Example 1) (1) Manufacturing of top pads Toluene diisocyanate (TDI), dicyclohexylmethane diisocyanate (H12MDI), polytetramethylene ether glycol (PTMEG), and diethylene glycol (DEG) were placed in a four-necked flask and reacted at 80°C for 3 hours to prepare a urethane-based prepolymer with a terminal NCO group content (NCO%) of 8% to 12% by weight.
[0167] A casting apparatus was prepared, equipped with tanks and input lines for supplying the raw materials, such as the urethane-based prepolymer, curing agent, and inert gas. Specifically, the urethane-based prepolymer prepared in step (1), curing agent (4,4'-methylenebis(2-chloroaniline), MOCA), solid-phase foaming agent (average particle size: 20 μm), inert gas (N2), and silicone-based surfactant (Evonik) were filled into the respective tanks. At this time, 1.5 parts by weight of the solid-phase foaming agent were added for every 100 parts by weight of the urethane-based prepolymer, and the urethane-based prepolymer and curing agent were added in an equivalent ratio of 1:1 and at a total rate of 10 kg / min.
[0168] Subsequently, the raw materials were introduced into the mixing head at a constant speed via each input line while being stirred (mixing head rotation speed: approximately 5000 rpm). A mold (1000 mm x 1000 mm x 3 mm) was prepared and preheated to 80°C, and the stirred mixture was extruded into the mold and reacted to obtain a solidified cake-like molded body. Then, the upper and lower ends of the molded body were cut to produce a top pad. At this time, the top pad had a thickness of 2 mm, a hardness of 58.8 Shore D, a specific gravity of 0.79 g / cc, and an elongation of 111%.
[0169] (2) Manufacturing of sub-pads A nonwoven fabric made of polyester fibers was impregnated with polyurethane resin and dried at 140°C for 10 minutes to produce a nonwoven fabric layer with a thickness of approximately 0.7 mm. Polyurethane resin was cast onto the nonwoven fabric layer and dried at 140°C for 10 minutes to form a suede layer with a thickness of approximately 0.8 mm, thereby producing a sub-pad (total thickness: 1.53 mm) consisting of a double structure of the nonwoven fabric layer and the suede layer. Both sides of the sub-pad were then sanded. Figure 1 shows a scanning electron microscope (SEM) image of the cross-section of the sub-pad of Example 1.
[0170] (3) Manufacturing of polishing pads After the top pad manufactured in step (1) undergoes surface milling and groove forming processes, the sub-pad manufactured in step (2) is placed on the lower part of the top pad, and the top pad and sub-pad are bonded together using hot melt adhesive to manufacture a polishing pad (total thickness: 3.55 mm). At this time, the sub-pad was bonded so that the suede layer of the sub-pad was in contact with the top pad. In addition, double-sided tape (model name: 442JS, 3M) was attached to the lower part of the sub-pad so that it could be attached to the platen of the CMP device.
[0171] (Comparative Example 1) (1) Manufacturing of top pads The top pad was manufactured using the same method as in Example 1.
[0172] (2) Manufacturing of sub-pads A sub-pad having a single-layer suede structure was manufactured by casting polyurethane resin onto a polyethylene terephthalate (PET) film and drying it at 140°C for 10 minutes to form a suede layer with a thickness of approximately 0.63 mm. The surface of the suede layer was then sanded. Figure 2 shows a scanning electron microscope (SEM) image of the cross-section of the sub-pad in Comparative Example 1.
[0173] (3) Manufacturing of polishing pads A polishing pad (total thickness: 2.65 mm) was manufactured using the same method as in Example 1 described above.
[0174] (Comparative Example 2) (1) Manufacturing of top pads The top pad was manufactured using the same method as in Example 1.
[0175] (2) Manufacturing of sub-pads A sub-pad having a single-layer nonwoven fabric structure was manufactured by impregnating a polyester fiber nonwoven fabric with polyurethane resin and drying it at 140°C for 10 minutes to form a nonwoven fabric layer with a thickness of approximately 1.30 mm. Then, both sides of the nonwoven fabric layer were sanded. Figure 3 shows a scanning electron microscope (SEM) image of the cross-section of the sub-pad in Comparative Example 2.
[0176] (3) Manufacturing of polishing pads A polishing pad (total thickness: 3.32 mm) was manufactured using the same method as in Example 1 described above.
[0177] <Physical properties of the sub-pad> (Experimental Example 1: Hardness) The hardness of the sub-pads manufactured in Example 1, Comparative Example 1, and Comparative Example 2 was measured. Specifically, the sub-pads were cut into 5 cm x 5 cm sections, stored at 25°C for 12 hours, and then the Shore D hardness was measured using a hardness tester.
[0178] (Experimental Example 2: Compression Ratio) The compression ratio was measured for the sub-pads manufactured in Example 1, Comparative Example 1, and Comparative Example 2. Specifically, the sub-pads were cut into 5 cm x 5 cm sections, and the thickness (A) was measured after placing an 85 g weight on them for 30 seconds using a Dial Thickness Gauge (129-E, YASUDA Co., Ltd.), and the thickness (B) was measured after placing an additional 800 g weight (85 g weight + 800 g weight) on them for 3 minutes. The compression ratio was then calculated using the following mathematical formula 3. [Math 3] Compression ratio (%) = [(AB) / A] × 100
[0179] (Experimental Example 3: Density) The density of the sub-pads produced in Example 1, Comparative Example 1, and Comparative Example 2 was measured according to ASTM D1622.
[0180] (Experimental Example 4: Compression Modulus) The compressive modulus of the sub-pads manufactured in Example 1, Comparative Example 1, and Comparative Example 2 was measured. Specifically, the sub-pads were cut into 5 cm x 5 cm sections, and the thickness (A) was measured using a Dial Thickness Gauge (129-E, YASUDA Co.) after placing an 85 g weight on them for 30 seconds, and the thickness (C) was measured after placing an additional 800 g weight (85 g weight + 800 g weight) on them for 3 minutes, then removing the 800 g weight and letting them stand for 1 minute. The compressive modulus of the sub-pads was then calculated using the following mathematical formula 4. [Math 4] Compression modulus = [C / A] × 100
[0181] <Physical properties of polishing pads> (Experimental Example 5: Polishing Rate) For the polishing pads of Example 1, Comparative Example 1, and Comparative Example 2, the polishing pads were fixed on the platen of the CMP apparatus, a silicon oxide film of a silicon wafer (diameter: 300 mm) was placed underneath, and the CMP process was performed to measure the polishing rate.
[0182] Specifically, the polishing load was adjusted to 4.0 psi, and the silicon oxide film was polished by rotating the platen at 150 rpm for 60 seconds while adding a calcined ceria slurry / silica slurry onto the polishing pad at a rate of 250 mL / min. After polishing, the silicon wafer was removed from the carrier, placed in a rotary spin dryer, washed with purified water, and then dried with nitrogen for 15 seconds. The difference in silicon oxide film thickness before and after polishing was measured using a spectroscopic interferometry thickness analyzer (SI-F80R, Kyence), and the polishing rate was calculated using the following mathematical formula 1. [Mathematics 1] Polishing rate (Å / min) = Change in film thickness before and after polishing (Å) / Polishing time (min)
[0183] Furthermore, in the polishing rate profile obtained by the polishing rate measurement described above, the gradient values were calculated at a distance of 85 mm to 95 mm from the center of the wafer. (Experimental Example 6: Polishing Flatness) For the polishing pads of Example 1, Comparative Example 1, and Comparative Example 2, the polishing pads were fixed on the platen of the CMP apparatus, a silicon oxide film of a silicon wafer (diameter: 300 mm) was placed underneath, and the CMP process was performed to measure the polishing flatness.
[0184] Specifically, after polishing using the same method as in Experimental Example 5, the in-plane film thickness of the wafer was measured at 98 locations, and the polishing flatness within the wafer surface (within wafer non-uniformity, WIWNU) was measured using the following mathematical formula 2. [Math 2] Polishing flatness (%) = (Standard deviation of polished thickness (Å) / Average polished thickness (Å)) × 100
[0185] [Table 1]
[0186] As can be seen from Table 1 above, the polishing pad of Example 1 exhibited superior polishing efficiency and polishing flatness in both aspects, as the polishing efficiency at a point 95 mm from the center of the wafer was greater than the polishing efficiency at a point 85 mm from the center of the wafer in the CMP process polishing efficiency profile for the silicon oxide film.
[0187] More specifically, while Comparative Examples 1 and 2, which include a sub-pad consisting of a single layer of suede or nonwoven fabric, as in the conventional method, showed a negative average gradient value in the CMP process polishing rate profile for silicon oxide films between 85mm and 95mm from the center of the wafer, the polishing pad of Example 1, which includes a double-layered sub-pad consisting of a nonwoven fabric layer and a suede layer, showed a positive average gradient value in the CMP process polishing rate profile for silicon oxide films between 85mm and 95mm from the center of the wafer, indicating a completely different trend in the polishing rate profile characteristics. In particular, while Comparative Examples 1 and 2 had large negative gradient values of approximately -30.948 and -20.311, Example 1 had a positive gradient value of approximately 7.3989, showing a smaller change compared to Comparative Examples 1 and 2, where the polishing rate drops sharply at the polishing pad edge, demonstrating superior polishing uniformity (see Figures 4 to 8).
[0188] Furthermore, the sub-pad of Example 1 had a lower density relative to its thickness compared to the sub-pads of Comparative Examples 1 and 2. As a result, the polishing rate was uniformly distributed with respect to the distance from the center of the wafer in the CMP process polishing rate profile, resulting in superior polishing flatness. [Explanation of symbols]
[0189] 100: Polishing pad 200: Platen 300: Conditioner 400: Polishing slurry 510: Polishing head 520: Career 600: Semiconductor substrate (wafer)
Claims
1. A top pad that comes into contact with the wafer to perform polishing, This includes a sub-pad located on one side of the top pad, Polishing pads that satisfy the following formula 1: [Formula 1] RR 85 <RR 95 In the above formula 1, RR 85 This is the polishing rate (Å / min) at a point where the distance from the center of the wafer is 85 mm in the CMP process polishing rate profile for silicon oxide films. RR 95 This represents the polishing rate (Å / min) at a point where the distance from the center of the wafer is 95 mm in the CMP process polishing rate profile for silicon oxide films.
2. The polishing pad according to claim 1, wherein in the CMP process polishing rate profile for a silicon oxide film, the average gradient value between 85 mm and 95 mm from the center of the wafer is a positive number.
3. The polishing pad according to claim 1, wherein the average gradient value between 85 mm and 95 mm from the center of the wafer in the CMP process polishing rate profile for a silicon oxide film is 0.5 or more.
4. The polishing pad has a polishing flatness (WIWNU) of 10% or less relative to the oxide. The polishing pad according to claim 1, wherein the polishing rate difference (ΔRR) calculated by the following formula 2 is 200 Å / min or less: [Formula 2] ΔRR=RR 95 -RR 85 In the above formula 2, RR 85 This is the polishing rate (Å / min) at a point where the distance from the center of the wafer is 85 mm in the CMP process polishing rate profile for silicon oxide films. RR 95 This represents the polishing rate (Å / min) at a point where the distance from the center of the wafer is 95 mm in the CMP process polishing rate profile for silicon oxide films.
5. The polishing pad according to claim 1, wherein when polishing the silicon oxide layer of a silicon wafer with a ceria slurry using the aforementioned polishing pad, the average polishing rate according to the following mathematical formula 1 is 2100 Å / min to 3500 Å / min: [Mathematics 1] Average polishing rate (Å / min) = Change in film thickness before and after polishing (Å) / Polishing time (minutes).
6. The sub-pad comprises a nonwoven fabric layer and a suede layer. The suede layer is located on one surface of the top pad, The polishing pad according to claim 1, wherein the thickness ratio of the nonwoven fabric layer to the suede layer is 1:0.5 to 2.
7. The aforementioned sub-pad is A thickness of 0.5 mm to 2.5 mm, Hardness ranges from 60 Shore D to 90 Shore D, Compression ratio of 5% to 15%, 0.25 g / cm 3 to 0.7 g / cm 3 of density, It has a compressive modulus of 70% to 90%. The aforementioned top pad is Hardness ranges from 50 Shore D to 65 Shore D, 0.6 g / cm 3 ~0.9 g / cm 3 The specific gravity and 15 N / mm 2 ~25 N / mm 2 The tensile strength and The polishing pad according to claim 1, having an elongation rate of 90% to 130%.
8. (1) A step of manufacturing a top pad using a top pad composition comprising a urethane-based prepolymer, a foaming agent, and a curing agent, (2) A step of manufacturing a sub-pad including a nonwoven fabric layer and a suede layer, (3) The step of manufacturing a polishing pad by bonding the top pad and the sub pad together, The polishing pad satisfies the following formula 1, a method for manufacturing the polishing pad: [Formula 1] RR 85 <RR 95 In the above formula 1, RR 85 This is the polishing rate (Å / min) at a point where the distance from the center of the wafer is 85 mm in the CMP process polishing rate profile for silicon oxide films. RR 95 This represents the polishing rate (Å / min) at a point where the distance from the center of the wafer is 95 mm in the CMP process polishing rate profile for silicon oxide films.
9. The aforementioned step (2) is, The steps include impregnating a nonwoven fabric with resin to produce a nonwoven fabric layer, A method for manufacturing an abrasive pad according to claim 8, comprising the step of casting a resin onto one surface of the nonwoven fabric layer to form a suede layer.
10. A method for manufacturing a semiconductor device, comprising the step of polishing the surface of a semiconductor substrate using the polishing pad of claim 1.
Citation Information
Patent Citations
KR2018-0044771